METHODS OF CORRECTING PSYCHIC DEPRIVATION IN THE PUPILS OF THE “KINDNESS” HOUSE - Rustamova Manzura Ne'matjanovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article will talk about the specific psychological characteristics of the Breeders of the Houses of “kindness”, the tasks set before the state and society in preparing them for an independent life as a full-fledged person. Ham also touched on the work activities of a practical psychologist with children and adolescents brought up in orphanages.